KinModRe: A Repository of Whole Cell Kinetic Models - Nursakinah Mohamed-Khalid; Nicholas Wei Jun Liew; Felice Jia Ying Ng; Ting Yi Lim; Farhana Abdul-Samathu; Maurice HT Ling (Journal of Clinical Immunology & Microbiology, 2026)
Whole-cell kinetic models represent cellular processes as mechanistic reaction networks governed by kinetic rate laws, enabling simulation of metabolic dynamics and system-level cellular behaviour. Despite their scientific value, executable implementations of such models remain relatively scarce and many published models are distributed only as static descriptions within manuscripts. To address this limitation, we present KinModRe (https://github.com/mauriceling/kinmodre), a repository of executable whole-cell kinetic models derived from modelling work using the AdvanceSyn Toolkit. The repository currently contains more than 130 models, including 31 de novo / ab initio kinetic reconstructions with the rest converted from genome-scale metabolic networks. Model sizes range from small pathway-level systems to large knowledge-base reconstructions containing tens of thousands of metabolites. Each model includes reaction definitions, kinetic rate laws, parameter sets and runnable simulation scripts. By publishing executable kinetic models as reusable computational artefacts, KinModRe provides a resource for research, methodological development and education in mechanistic systems modelling.